Spatial temporal patterns and driving factors of industrial pollution and structures in the Yangtze River Economic Belt. (September 2022) - Wang, Yazhu; Duan, Xuejun; Wang, Lingqing; Zou, Hui
Abstract: The conflict between industrial development and environmental pollution is global. This study quantitatively analyzes the temporal and spatial changes, spatial effects and determinants of industrial pollution discharge in the Yangtze River Economic Belt through two main indicators: wastewater and SO2 . Analyze the spatial coupling relationship between industrial agglomeration and pollution emission and the characteristics of industrial structure in different regions. The analysis shows that industrial emissions in the Yangtze River Economic Belt first increased and then decreased during the period 2003–2019. Industrial pollution spread from large to small and medium cities and shifted from downstream to upstream. Moreover, a positive correlation exists between industrial pollution discharge and per capita GDP, secondary industry proportion, population density, and energy use. Meanwhile, scientific and technological progress and environmental regulations are associated with industrial pollution reduction. Since the Yangtze River Economic Belt was still in the industrialization stage and had not yet reached a turning point on the Environmental Kuznets Curve. The "pollution refuge" phenomenon was evident in the Belt, where underdeveloped areas in the central and western regions accommodated portions of highly polluting industries from the eastern areas through "regional competition" and "policy depression." The industrial agglomeration and pollution antagonistic zones were dominated by polluting industries; environmental risks were greatest in these areas. The upstream and downstream of the YREB play the negative and positive environmental externalities of industrial agglomeration, respectively. Thus, differential control measures should be formulated according to different regions, industrial pollutants, and polluting industries to improve environmental quality. Highlights: Industrial emissions first increased and then decreased during the period 2003–2019. Industrial pollution spread from large to small and medium cities and shifted from downstream to upstream. Economic development and population agglomeration increased pollution. The "crowding effect" of industrial agglomeration intensifies the emission of pollutants.